Review on magnetocaloric high-entropy alloys: Design and analysis methods - Law, Jia Yan; Franco, Victorino (Journal of materials research, 2023)
The search for high-performance functional alloys with improved service life and reliability entails the optimization of their mechanical properties. Recently, the high-entropy alloy (HEA) design concept has found new alloys with excellent mechanical properties. It utilizes multiprincipal elements to yield high configurational entropy of mixing, entailing a large compositional freedom with wide window of opportunities for property exploration. Their functional properties are usually modest when compared to conventional materials. The discovery of HEAs with optimal combination of mechanical and functional properties would be a leap forward in the reliability of functional devices. This review article focuses on magnetocaloric HEAs, the design approaches, and the appropriate analysis methods for their performance. We will highlight the efficient strategic search within the vast HEA space, which has been instrumental for significantly enhancing MCE performance, closing the pre-existing gap between magnetocaloric HEAs and high-performance conventional magnetocaloric materials. Outlook for future directions will also be included. Graphical abstract